Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/00005110-200605000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Face of Resistance

Abstract: The nurses interviewed described situations in their work lives, where they felt that they performed an act of resistance because of unfair treatment, abuse of power, or ethical concerns. It often took courage to do so, but the acts had mainly positive effects on them and their institutions. It is theorized that resistance may actually be positive for both the staff nurse and the organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The authors of these articles addressed ethical issues and challenges faced by nurse leaders, 18,19 and the ethical dilemma of 12-h shifts. 20 A few others included ethical dimensions, for example, positive aspects of nurse resistance, 21 organizational respect and justice for nurses, 22 and servant leadership. 23 Some articles contained “values” in the title, but these rarely translated into ethical values.…”
Section: Literature Review—decades Of Neglect?mentioning
confidence: 99%
“…The authors of these articles addressed ethical issues and challenges faced by nurse leaders, 18,19 and the ethical dilemma of 12-h shifts. 20 A few others included ethical dimensions, for example, positive aspects of nurse resistance, 21 organizational respect and justice for nurses, 22 and servant leadership. 23 Some articles contained “values” in the title, but these rarely translated into ethical values.…”
Section: Literature Review—decades Of Neglect?mentioning
confidence: 99%
“…Being a courageous nurse meant knowledge of one’s own values and acting on them. 25,29,42,46 51 Upholding the commitment to values required courage because it left oneself open to criticism from others and open to consequences personally and professionally. 25,42,52,53…”
Section: Resultsmentioning
confidence: 99%
“… 77 While resistance was sometimes ineffective at changing the situation for individual nurses, it often brought about systemic change. 78 A recent study found that nurses use resistance to practice morally, to open spaces where dominant discourses could be challenged, and where they could practice on their own terms, in a morally authentic way. 79 Nurses should then feel ‘comfortable with their own appetite for power, implement their power strategies, and after feel satisfied or “full” because they did what they believed was necessary’ (p. 186).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“… 37 For Garon, this resistance can be an ‘ethical safety valve’ that can even be beneficial to administrators, since it contributes to safer work environments, and allows them to be informed of nurses’ concerns (p. 249). 78 Research needs to continue documenting how nurses resist in the face of unjust practices, especially as working conditions continue to be impacted by healthcare organizations that normalize chronic work overload, an increasing speed and pace of work 43 and systematically resort to mandatory overtime. 80 By capturing these informal narratives of nurses in different settings, we can add important data to motivate democratic change in different healthcare settings and in the political sphere.…”
Section: Implications For Research and Practicementioning
confidence: 99%